Flagellar glycosylation - a new component of the motility repertoire? - Logan, Susan M (Microbiology (Society for General Microbiology), 2006)
Institute for Biological Sciences, National Research Council, Ottawa, Ontario K1A OR6, Canada Correspondence Susan M. Logan susan.loganatnrc-cnrc.gc.ca The biosynthesis, assembly and regulation of the flagellar apparatus has been the subject of extensive studies over many decades, with considerable attention devoted to the peritrichous flagella of Escherichia coli and Salmonella enterica . The characterization of flagellar systems from many other bacterial species has revealed subtle yet distinct differences in composition, regulation and mode of assembly of this important subcellular structure. Glycosylation of the major structural protein, the flagellin, has been shown most recently to be an important component of numerous flagellar systems in both Archaea and Bacteria, playing either an integral role in assembly or for a number of bacterial pathogens a role in virulence. This review focuses on the structural diversity in flagellar glycosylation systems and demonstrates that as a consequence of the unique assembly processes, the type of glycosidic linkage found on archaeal and bacterial flagellins is distinctive.